2017
DOI: 10.1186/s13098-017-0261-x
|View full text |Cite
|
Sign up to set email alerts
|

Worse inflammatory profile in omnivores than in vegetarians associates with the gut microbiota composition

Abstract: AimsTo describe the abundance of major phyla and some genera in the gut microbiota of individuals according to dietary habits and examine their associations with inflammatory markers, insulin resistance, and cardiovascular risk profile.MethodsA total of 268 non-diabetic individuals were stratified into groups of dietary types (strict vegetarians, lacto-ovo-vegetarians, and omnivores). The taxonomic composition and phylogenetic structure of the microbiota were obtained through the analysis of the 16S rRNA gene.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
2
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 56 publications
3
52
2
4
Order By: Relevance
“…Dietary patterns that are rich in unrefined plant foods have been demonstrated to reduce CRP levels in various studies . A study from 2017 found significantly higher CRP levels in omnivores than in vegans (1.1 mg/L vs 0.5 mg/L; P ‐level: 0.007) . Furthermore, a more recent meta‐analysis investigating the association between vegetarian diets and inflammatory biomarkers found that a vegetarian diet might be a useful approach to manage inflammation in the long term …”
Section: Risk Factor Modification Through Dietary Modificationmentioning
confidence: 99%
“…Dietary patterns that are rich in unrefined plant foods have been demonstrated to reduce CRP levels in various studies . A study from 2017 found significantly higher CRP levels in omnivores than in vegans (1.1 mg/L vs 0.5 mg/L; P ‐level: 0.007) . Furthermore, a more recent meta‐analysis investigating the association between vegetarian diets and inflammatory biomarkers found that a vegetarian diet might be a useful approach to manage inflammation in the long term …”
Section: Risk Factor Modification Through Dietary Modificationmentioning
confidence: 99%
“…These studies showed conflicting results. Whereas Franco-de-Moraes et al 16 observed higher CRP levels in omnivores compared to vegans, Šebeková et al 15 noticed no differences in CRP levels. The latter is in line with our results.…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, there are no studies, which perform comprehensive analyses to investigate the association of a vegan diet on the inflammatory profile. Accordingly, until now, only two studies provide data on inflammatory biomarkers in vegans (n = 9) 15 or strict vegetarians (animal products less than once a month, n = 66) 16 as small subgroups, while mainly investigating advanced glycation end products 15 or gut microbiota composition 16 in a vegetarian population. These studies showed conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…Gut and root microbiomes. TAG.ME performance was further compared with DADA2 on two real-world scenarios involving gut [21] and roots samples [22]. In these cases, both DADA2+RDP and DADA2+SILVA versions were compared.…”
Section: Resultsmentioning
confidence: 99%
“…Two published datasets were used to evaluate the performance of sequenced data. The dataset available under the accession PRJEB19103 [21] represents the human gut environment, and accession PRJEB15671 [22] represents the root ecosystem. The amplicon sequence variants (ASVs) were identified using the DADA2 workflow.…”
Section: Test Data Sets Dada2 Classification Into Species-level Relimentioning
confidence: 99%